Ripples: What to Expect When You Serve on a Bioethics Commission - Murray, Thomas H. (The Hastings Center report, 2017)
Cloning was the issue that put the National Bioethics Advisory Commission on the map, but the first clue that NBAC would address cloning was a terse fax from the White House to each of us who served on the Commission. The fax noted that with the birth of the sheep named Dolly, mammalian cloning was now a reality, and it tasked NBAC with providing advice on the ethics of human cloning and how the nation should respond to it. We were given ninety days to report our findings. That's a very tight deadline for a report written by a committee, but we met it, and along the way, I learned important lessons. My goal in this essay is to share what I learned at the ramparts of what I will call, with apologies to George Lucas, the Cloning Wars and through NBAC's work on five additional reports.